Pembangunan prototaip sistem jadual waktu sekolah - Ibrahim, Suhaimi (Penerbit UTM Press, 1996)
This paper discusses the activities of the school timetable preparation. The study was conducted on a number of secondary schools in Kelang Valley and a prototype was developed, to identify the user requirements of the system. The developed system was aimed at assisting the schools in the time table preparation. This paper does not discuss on the scheduling technique but rather a user interface that was developed in Visual Basic.